Pelatihan Pembuatan Alat Bantu Pengajaran IPA Pada Percobaan Bandul Matematis , Tekanan Hidrostatis, Pengukuran Tekanan Zat Cair Serta Kecepatan Dan Percepatan Bagi Guru-Guru Ipa Sekolah Sahabat Sabah Malaysia - Ermawati, Imas Ratna (International Journal of Community Service Learning, 2022)
This community partnership program aims for downstream activities and a science teacher training mentoring program at ULC Sekolah Sahabat Sabah Malaysia. In addition, based on observations from previous research, information was obtained about the lack of science practicum subjects and the procurement of teaching aids is very dependent on the ability of the school and the creativity of the teacher concerned. In this regard, science teachers, especially physics, biology and chemistry are required to have creativity and skills in making and using teaching aids, in this case also produced a module for the use of teaching aids and videos for making teaching aids. Method what is used in this activity is a training (workshop), namely, providing training in making simple science teaching aids, then mentoring is carried out. The number of participants was 37 teachers in the plantation area or ULC at the Sabah Malaysia Friendship School which was carried out online using a zoom meeting. This activity is carried out for 1 day with 8 JP. Participants' responses were measured using a questionnaire at the end of the training. Participants said that the material discussed in the training said 82.21% was very good important, and 17.79% important. This condition shows that this material is right on target and useful for the audience of participants. The informants conveyed the training method 80.81% said they were very satisfied and 19.19% said they were satisfied with the training method. In addition, the response of participants to the resource persons/training instructors was 84.92 % who stated that they were very satisfied and 15.08 % of the participants stated that they were satisfied, so it can be concluded that the training used was very good. This activity is expected to increase knowledge, skills in making props by utilizing nature and the surrounding environment.